THE EFFECT OF CHITOSAN ORININATED FROM THE CARAPACE OF T. ANOMALA SHRIMP AS HEAVY METAL ABSORBERS ON GRAVESTONE - Sastiwi Sastiwi; Sukirno Mus; Bustari Hasan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT T. anomala is a type of shrimp that commonly found in the muddy areas of mangrove along the coastalareaSelatPanjang. This study aims to determine the effectiveness of the chitosan in absorbing heavy metals in gravestones.Carapace from T. anomala is used as raw material of chitosan.The carapace was taken and then washed, dried, refined, demineralization, de-preoteinated, deasitelation and was tested of heavy metals Pb and Cd in gravestone using AAS.The characteristics of chitosan T. anomala were semi-transparent cream color, in the form of amorphous solid, and odorless with yield value, moisture content, ash content, nitrogen content and the degree of deacetylation 17.5%, 6.74% (gw), 4.32% (dw) , 7.55%, and 71% respectively.Based on reduction values of Pb and Cd heavy metals, the concentration of K3% was the best concentration with the reduction values of 84.56% and 50.00%, respectively. These values indicate that the effectiveness of chitosan in absorbing is strong.Key words: Mud lobster, chitosan, heavy metals Pb and Cd.